Self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anticorrosive paint and coating

By combining the modified PCD-MXene filler with aqueous epoxy resin, the problem of easy oxidation of Ti3C2Tx MXene in the prior art is solved, and the high corrosion resistance, stability and self-healing properties of the coating are achieved, and the overall performance of the anticorrosion coating is improved.

CN119775855APending Publication Date: 2025-04-08NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411922809.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The lack of antioxidant and stable modified Ti3C2Tx MXene's self-healing aqueous epoxy resin anticorrosion coating in the prior art makes MXene easy to oxidize in actual use, reducing its stability and anticorrosion properties.

Method used

By preparing the modified PCD-MXene filler, the reaction of lithium fluoride and Ti3AlC2 is used to generate Ti3C2Tx MXene, and the CD and 5-chloro-1,10-phenanthroline are compounded with MXene through hydrothermal reaction and ultrasonic treatment to form PCD-MXene filler with high aspect ratio and large surface area, and anticorrosion coatings are prepared by combining aqueous epoxy resin and curing agent.

Benefits of technology

The modified PCD-MXene filler improves the corrosion resistance and stability of the coating, has self-healing properties, and can form a protective film to prevent direct contact between the corrosive media and the metal surface, reduces the oxidative corrosion of the metal, and improves the oxidation and chemical stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775855A_ABST
    Figure CN119775855A_ABST
Patent Text Reader

Abstract

The invention relates to a self-healing anti-oxidation Phen / CD-MXene / water-borne epoxy resin anticorrosive paint and a coating, relates to the technical field of anticorrosive paints, and aims to solve the problem of lack of anti-oxidation and stability modified Ti3C2Tx MXene self-healing water-borne epoxy resin anticorrosive paints in the prior art. The anticorrosive paint provided by the invention is prepared from the following components in parts by mass: 0.3 to 0.8 part of PCD-MXene filler, 35 to 40 parts of waterborne epoxy resin, 45 to 55 parts of curing agent, 0.025 to 0.05 part of body filler and 0.02 to 0.1 part of additive. The preparation method comprises the following steps: dispersing CD powder into n-butyl alcohol, adding Ti3C2Tx MXene powder and ascorbic acid to obtain a mixed solution, adding the mixed solution into a solution consisting of 3-amino-1-propanol, NaOH and 5-chloro-1, 10-phenanthroline, and stirring, centrifuging, washing and drying in a nitrogen atmosphere and an ice-water bath to obtain PCD-MXene powder. The anti-corrosion coating can effectively prevent a corrosion medium from being in direct contact with the metal surface; and the permeation rate of hydrogen ions and oxygen on the metal surface is reduced, and oxidation corrosion of metal is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a self-healing anti-oxidation Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating and coating. Background Art

[0002] Metal corrosion is one of the major industrial problems. In order to slow down metal corrosion, common protective measures include coating, plating, anodic protection and other methods. Among them, coating the metal surface with epoxy anti-corrosion coating is simple to operate and low in cost, and is currently a commonly adopted anti-corrosion measure. However, traditional epoxy coatings have disadvantages such as high porosity, low hardness, and easy cracking. MXene, especially Ti 3 C 2 T x MXene, with excellent flexibility, good electronic conductivity and excellent mechanical properties, is one of the most commonly used two-dimensional materials and has broad application prospects in the fields of energy, sensing, catalysis and corrosion protection. Adding two-dimensional MXene to water-based epoxy resin can reduce the micropores and cracks of the coating and enhance the corrosion resistance of the coating. However, due to the natural stacking tendency and low oxidation stability of MXene, its stability is greatly reduced. At present, most of the modification of MXene is considered to modify its dispersibility, while the modification of its oxidizability mainly adopts edge protection and inert gas low-temperature protection to slow down the oxidation process of MXene. However, edge protection affects the conductivity and mechanical properties of MXene. At the same time, it is difficult to always maintain a low temperature and inert gas environment in its actual use, which leads to oxidation of MXene. Self-healing technology mainly achieves self-repair by adding corrosion inhibitors or microcapsules loaded with healing agents to the coating. It can make up for the tiny holes and gaps formed by the agglomeration of coating fillers and hinder the invasion of corrosive media. However, the current self-healing coatings generally have problems such as high R&D and production costs and complex preparation processes. In addition, the healing effect of the coating is greatly affected by the environment and temperature. At higher or lower temperatures, the healing ability is greatly reduced. Therefore, it is urgent to develop a new type of anti-oxidation Ti 3 C 2 T x MXene composite fillers to prepare waterborne epoxy resin anti-corrosion coatings with self-healing properties. Summary of the invention

[0003] The technical problems to be solved by the present invention are:

[0004] The existing technology lacks anti-oxidation and stability modified Ti 3 C 2 T x MXene-based self-healing waterborne epoxy anti-corrosion coating.

[0005] The present invention adopts the following technical solutions to solve the above technical problems:

[0006] The present invention provides a self-healing anti-oxidation Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating, wherein the anti-corrosion coating comprises, by mass: 0.3-0.8 parts of PCD-MXene filler, 35-40 parts of waterborne epoxy resin, 45-55 parts of curing agent, 0.025-0.05 parts of body filler, and 0.02-0.1 parts of auxiliary agent;

[0007] The preparation method of the PCD-Mxene comprises the following steps:

[0008] Step 1: Add lithium fluoride to concentrated hydrochloric acid. After the reaction is complete, add Ti 3 AlC 2 The etching reaction was carried out while stirring. After the reaction was completed, the precipitate was washed with deionized water and centrifuged. The precipitate was collected and added to deionized water. The precipitate was placed in an ice water bath and ultrasonicated for 1 h under a nitrogen atmosphere. The precipitate was centrifuged and the suspension was collected. The Ti 3 C 2 T x MXene powder;

[0009] Step 2: Add salicylic acid and banana peel powder into deionized water, stir, and adjust the solution to neutrality with ammonia water; transfer the solution to an autoclave for hydrothermal reaction. After the reaction is completed, purify it with deionized water in a dialysis bag and freeze-dry to obtain CD powder;

[0010] Step 3: Add 3-amino-1-propanol and NaOH to DMF, then add 5-chloro-1,10-phenanthroline, heat and stir until all dissolved to obtain the first solution; add CD powder to n-butanol, ultrasonicate, add Ti 3 C 2 T x MXene powder and ascorbic acid are stirred evenly to obtain a mixed solution; the mixed solution is added to the first solution, stirred under a nitrogen atmosphere and an ice water bath, centrifuged, washed, and dried to obtain PCD-MXene powder;

[0011] Step 4: Mix PCD-MXene, water-based epoxy resin, curing agent, physical filler and additives according to mass proportions to obtain PCD-MXene / WEP anti-corrosion coating.

[0012] Furthermore, in step 1, lithium fluoride and Ti 3 AlC 2 The mass ratio is (1-2):(0.5-1.5).

[0013] Furthermore, in step 2, the mass ratio of salicylic acid to banana peel powder is (1-3): (2-4).

[0014] Furthermore, in step 3, the ratio of 3-amino-1-propanol to NaOH is 1 ml: 0.75 g, and NaOH is mixed with 5-chloro-1,10-phenanthroline, CD, Ti 3 C 2 T x The mass ratio of MXene and ascorbic acid is 30:30:16:40:1.

[0015] Furthermore, the temperature of the hydrothermal reaction in step 2 is 180-200°C.

[0016] Furthermore, the ultrasonic treatment time in step 3 is 5 to 10 minutes.

[0017] Furthermore, the water-based epoxy resin is CYDW-100.

[0018] Furthermore, the curing agent is at least one of CYDHD-220, CYDHD-520 or CYDHD-625 curing agents.

[0019] Furthermore, the auxiliary agent is at least one of a defoaming agent, a wetting agent or a dispersant.

[0020] Furthermore, the physical filler is at least one of talcum powder, mica powder or bentonite.

[0021] The present invention also provides a self-healing anti-oxidation and anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating described in any one of the above technical solutions.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The modified PCD-MXene has a high aspect ratio and a large surface area, and has good compatibility with water-based epoxy resin. It effectively exerts the physical barrier properties of PCD-MXene, slows down the penetration of corrosive media, and thus improves the corrosion resistance and stability of the coating. 2. When the corrosive ions penetrate into the coating, the CD and 5-chloro-1,10-phenanthroline loaded on the surface of PCD-MXene form coordination bonds with metal ions, and form a protective film through adsorption, so that the coating has a certain self-healing property, preventing the direct contact between the corrosive medium and the metal surface; reducing the penetration rate of hydrogen ions and oxygen on the metal surface, and reducing the oxidative corrosion of the metal. 3. PCD-MXene has a large number of oxygen-containing functional groups, which form chemical bonds or hydrogen bonds with the polymer substrate in the coating, thereby enhancing the bonding force between the coating and the substrate. PCD-MXene has good antioxidant and chemical stability, which can improve the resistance of the coating to chemical substances. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 FTIR spectrum of PCD-MXene in the embodiment of the present invention;

[0025] Figure 2 : XRD diagrams of PCD-MXene and MXene in the embodiments of the present invention;

[0026] Figure 3 This is a comparison chart of the PCD-MXene and MXene dispersions in the embodiments of the present invention after being placed for 30 days;

[0027] Figure 4 The XRD diagram of the PCD-MXene and MXene dispersions in the embodiments of the present invention after being placed for 30 days;

[0028] Figure 5 It is a Tafel curve diagram of the anti-corrosion coating in an embodiment of the present invention immersed in a 3.5wt% NaCl solution for 90 days;

[0029] Figure 6 These are the EIS graphs of the anti-corrosion coating scratches in an embodiment of the present invention after being immersed in a 3.5wt% NaCl solution for 0 h and 48 h. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] In a typical embodiment of the present invention, a self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating is provided, which includes, by mass: 0.3-0.8 parts of PCD-MXene filler, 35-40 parts of waterborne epoxy resin, 45-55 parts of curing agent, 0.025-0.05 parts of physical filler, and 0.02-0.1 parts of auxiliary agent; the curing agent is preferably at least one of CYDHD-220, CYDHD-520 or CYDHD-625 type curing agents; the auxiliary agent is preferably at least one of a defoaming agent, a wetting agent or a dispersant; the physical filler is preferably at least one of talc powder, mica powder or bentonite.

[0033] In a typical embodiment of the present invention, a method for preparing PCD-Mxene is provided, comprising the following steps:

[0034] Step 1: Add lithium fluoride to concentrated hydrochloric acid. After the reaction is complete, add Ti 3 AlC 2 The etching reaction was carried out while stirring. After the reaction was completed, the precipitate was washed with deionized water and centrifuged. The precipitate was collected and added to deionized water. The precipitate was placed in an ice water bath and ultrasonicated for 1 h under a nitrogen atmosphere. The obtained sample was centrifuged, the suspension was collected, and Ti was obtained after freeze-drying. 3 C 2 T x MXene powder;

[0035] Step 2: Add salicylic acid and banana peel powder into deionized water, stir, and adjust the solution to neutrality with ammonia water; transfer the solution to an autoclave for hydrothermal reaction. After the reaction is completed, purify it with deionized water in a dialysis bag and freeze-dry to obtain CD powder;

[0036] Step 3: Add 3-amino-1-propanol and NaOH to DMF, then add 5-chloro-1,10-phenanthroline powder, heat and stir until completely dissolved to obtain the first solution; add CD powder to n-butanol, ultrasonicate, and add Ti 3 C 2 T x MXene powder and ascorbic acid are stirred evenly to obtain a mixed solution; the mixed solution is added to the first solution, stirred under a nitrogen atmosphere and an ice water bath, centrifuged, washed, and dried to obtain PCD-MXene powder;

[0037] Step 4: Mix PCD-MXene, water-based epoxy resin, curing agent, bentonite, talc, defoaming agent and dispersant according to mass proportions to obtain PCD-MXene / WEP anti-corrosion coating.

[0038] The present invention improves the oxidation stability and dispersibility of MXene by encapsulating and modifying it. When the corrosive medium penetrates into the coating, PCD-MXene can effectively exert its physical barrier performance. 5-Chloro-1,10-phenanthroline can capture iron ions to form a complex, fill the damaged part of the coating, and make the coating have self-healing properties. CD in PCD-MXene reacts with iron ions to form CD-Fe 3+ , adsorbed on the metal substrate, further slowing down metal corrosion. At the same time, the modified MXene filler can improve the mechanical properties and anti-corrosion properties of the coating, thereby obtaining an anti-corrosion coating with stable performance and long service life.

[0039] In order to improve the uniformity of the mixing of the raw materials, so as to obtain as uniform a PCD-MXene powder as possible, preferably in step 1, lithium fluoride and Ti 3 AlC 2 The mass ratio of salicylic acid and banana peel powder in step 2 is (1-3): (2-4); the ratio of 3-amino-1-propanol to NaOH in step 3 is 1 ml: 0.75 g, and the ratio of NaOH to 5-chloro-1,10-phenanthroline, CD, Ti 3 C 2 T x The mass ratio of MXene and ascorbic acid is 30:30:16:40:1.

[0040] In a typical embodiment of the present invention, the temperature of the hydrothermal reaction in step 2 is preferably 180-200°C.

[0041] In a typical embodiment of the present invention, the ultrasonic treatment time in step 3 is preferably 5 to 10 minutes.

[0042] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.

[0043] Example 1

[0044] Step 1: Add 1.5 g lithium fluoride to 30 mL concentrated hydrochloric acid. After the reaction is complete, add 1 g Ti 3 AlC 2 The etching reaction was carried out while stirring for 48 hours. After the reaction was completed, the precipitate was washed with deionized water and centrifuged. The precipitate was collected and dissolved in 100 mL of deionized water. The sample was ultrasonicated in a nitrogen ice water bath for 1 hour. The obtained sample was centrifuged at a rate of 5000 r / min for 1 hour. The suspension after centrifugation was collected and freeze-dried to obtain Ti 3 C 2 T x MXene powder;

[0045] Step 2: Add 2 g of salicylic acid and 3 g of banana peel powder to 50 mL of deionized water, stir for 30 min, and adjust the solution to neutrality with ammonia water; transfer the solution to a polytetrafluoroethylene-lined autoclave and heat at 180°C for 8 h. After the reaction is completed, purify it in a dialysis bag with deionized water for 36 h, and freeze-dry to obtain CD powder;

[0046] Step 3: Add 2 mL of 3-amino-1-propanol and 1.5 g of NaOH to 20 mL of DMF, then add 1.5 g of 5-chloro-1,10-phenanthroline powder, and stir to dissolve at 50 °C to obtain the first solution; add 0.8 g of CD powder to 10 mL of n-butanol, and after ultrasonic treatment; add 2 g of Ti3 C 2 T x MXene powder and 0.05 g ascorbic acid were stirred to obtain a uniform mixture; the mixture was added to the first solution using an ice water bath. 2 The PCD-MXene powder was obtained by magnetic stirring for 12 h under the following conditions, centrifugation, washing and drying;

[0047] Step 4: 0.3 g PCD-MXene, 35 g water-based epoxy resin CYDW-100, 45 g water-based curing agent CYDHD-220, 0.01 g bentonite, 0.015 g talc, 0.01 g defoaming agent, and 0.01 g dispersant were ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that in step 1, 1 g of lithium fluoride is added to 30 mL of concentrated hydrochloric acid, and after the reaction is completed, 0.5 g of Ti is added. 3 AlC 2 The etching reaction was carried out while stirring for 48 hours. After the reaction was completed, the precipitate was washed with deionized water and centrifuged. The precipitate was collected and dissolved in 100 mL of deionized water. The sample was ultrasonicated in a nitrogen ice water bath for 1 hour. The obtained sample was centrifuged at a rate of 5000 r / min for 1 hour. The suspension after centrifugation was collected and freeze-dried to obtain Ti 3 C 2 T x MXene powder.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that in step 1, 2 g of lithium fluoride is added to 30 mL of concentrated hydrochloric acid, and after the reaction is completed, 1.5 g of Ti is added. 3 AlC 2 The etching reaction was carried out while stirring for 48 hours. After the reaction was completed, the precipitate was washed with deionized water and centrifuged. The precipitate was collected and dissolved in 100 mL of deionized water. The sample was ultrasonicated in a nitrogen ice water bath for 1 hour. The obtained sample was centrifuged at a rate of 5000 r / min for 1 hour. The suspension after centrifugation was collected and freeze-dried to obtain Ti 3 C 2 T x MXene powder.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 1 is that in step 2, 1 g of salicylic acid and 2 g of banana peel powder are added to 50 mL of deionized water, stirred for 30 min, and then the solution is adjusted to neutrality with aqueous ammonia; the solution is transferred to a polytetrafluoroethylene-lined autoclave, heated at 190° C. for 8 h, and after the reaction is completed, purified in a dialysis bag with deionized water for 36 h, and freeze-dried to obtain CD powder.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 1 is that in step 2, 3 g of salicylic acid and 4 g of banana peel powder are added to 50 mL of deionized water, stirred for 30 min, and then the solution is adjusted to neutrality with aqueous ammonia; the solution is transferred to a polytetrafluoroethylene-lined autoclave, heated at 190° C. for 8 h, and after the reaction is completed, purified with deionized water in a dialysis bag for 36 h, and freeze-dried to obtain CD powder.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 1 is that in step 4, 0.35 g PCD-MXene, 36 g water-based epoxy resin CYDW-100, 47 g water-based curing agent CYDHD-220, 0.012 g bentonite, 0.015 g talc, 0.015 g defoaming agent, and 0.015 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0058] Example 7

[0059] The difference between this embodiment and embodiment 1 is that in step 4, 0.4 g PCD-MXene, 35 g water-based epoxy resin CYDW-100, 48 g water-based curing agent CYDHD-220, 0.014 g bentonite, 0.016 g talc, 0.017 g defoaming agent, and 0.015 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0060] Example 8

[0061] The difference between this embodiment and embodiment 1 is that in step 4, 0.4 g PCD-MXene, 40 g water-based epoxy resin CYDW-100, 52 g water-based curing agent CYDHD-220, 0.0145 g bentonite, 0.017 g talc, 0.0185 g defoaming agent, and 0.0185 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0062] Example 9

[0063] The difference between this embodiment and embodiment 1 is that in step 4, 0.5 g PCD-MXene, 40 g water-based epoxy resin CYDW-100, 50 g water-based curing agent CYDHD-220, 0.0175 g bentonite, 0.019 g talc, 0.02 g defoaming agent, and 0.02 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0064] Example 10

[0065] The difference between this embodiment and embodiment 1 is that in step 4, 0.55 g PCD-MXene, 35 g water-based epoxy resin CYDW-100, 48 g water-based curing agent CYDHD-220, 0.017 g bentonite, 0.0175 g talc, 0.025 g defoaming agent, and 0.025 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0066] Embodiment 11

[0067] The difference between this embodiment and embodiment 1 is that in step 4, 0.6 g PCD-MXene, 40 g water-based epoxy resin CYDW-100, 52 g water-based curing agent CYDHD-220, 0.0185 g bentonite, 0.02 g talc, 0.03 g defoaming agent, and 0.03 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0068] Example 12

[0069] The difference between this embodiment and embodiment 1 is that in step 4, 0.7 g PCD-MXene, 38 g water-based epoxy resin CYDW-100, 49 g water-based curing agent CYDHD-220, 0.02 g bentonite, 0.02 g talc, 0.035 g defoaming agent, and 0.04 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0070] Example 13

[0071] The difference between this embodiment and embodiment 1 is that in step 4, 0.75 g PCD-MXene, 40 g water-based epoxy resin CYDW-100, 52 g water-based curing agent CYDHD-220, 0.025 g bentonite, 0.022 g talc, 0.045 g defoaming agent, and 0.05 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0072] Embodiment 14

[0073] The difference between this embodiment and embodiment 1 is that in step 4, 0.8 g PCD-MXene, 40 g water-based epoxy resin CYDW-100, 55 g water-based curing agent CYDHD-220, 0.023 g bentonite, 0.025 g talc, 0.05 g defoaming agent, and 0.045 g dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that in step 4, 40 g of waterborne epoxy resin CYDW-100, 52 g of waterborne curing agent CYDHD-220, 0.0145 g of bentonite, 0.017 g of talc, 0.0185 g of defoaming agent, and 0.0185 g of dispersant are ultrasonically mixed for 20 min to obtain a PCD-MXene / WEP anti-corrosion coating.

[0076] The PCD-MXene of Example 1 was subjected to FTIR spectroscopy detection, as shown in FIG. Figure 1 As shown in the figure, it can be seen that there are obvious CN bonds and Ti-OC bonds in PCD-MXene, which indicates that Ti 3 C 2 T x MXene was successfully composited with CD, and the surface was successfully modified by phenanthroline.

[0077] PCD-MXene and Ti obtained in Example 1 3 C 2 T x MXene powder was subjected to XRD test, such as Figure 2 As shown, it can be seen that Ti 3 C 2 T x MXene has an obvious characteristic peak at (002), which indicates that Ti 3 C 2 T x MXene was successfully prepared. At the same time, the characteristic peak of CD (i.e., carbon material) at (002) can be observed in PCD-MXene, and phenanthroline did not destroy its crystal structure.

[0078] PCD-MXene and Ti 3 C 2 T x The MXene dispersions were placed for 30 days. Figure 3 As shown in Figure 2, it can be seen that the PCD-MXene dispersion still has good dispersibility after being placed at room temperature for 30 days. 3 C 2 T xThe MXene dispersion showed obvious degradation after 30 days of storage, and more sediment appeared at the bottom, which indicated that the stability and dispersibility of the filler were poor.

[0079] The PCD-MXene and Ti 3 C 2 T x The MXene dispersion was subjected to XRD testing, and the results were as follows: Figure 4 As shown in the figure, it can be seen that after PCD-MXene is placed for 30 days, the XRD peak does not change significantly, which indicates that PCD-MXene has good stability and dispersibility. 3 C 2 T x After the MXene dispersion was placed for 30 days, obvious TiO 2 Characteristic peak, which indicates that Ti 3 C 2 T x MXene is severely oxidized.

[0080] The performance of the anticorrosive coatings prepared in Examples 1 to 14 and Comparative Example 1 was tested. The surface of the mild steel was polished, and then the surface oil was removed with anhydrous ethanol, and then dried in an oven. The PCD-MXene / WEP anticorrosive coating prepared in the above example was evenly coated on the surface of the mild steel using an applicator, and then placed at room temperature for 48 hours, and then placed in a 40°C oven for drying for 3 to 5 hours to obtain a metal coating.

[0081] The metal test piece of Example 8 was placed in a 3.5wt% NaCl solution for Tafel polarization test. The electrochemical workstation adopted a three-electrode system, with graphite as the auxiliary electrode, a saturated Ag / AgCl electrode as the reference electrode, and a low-carbon steel coating as the working electrode. The test conditions were room temperature. Figure 5 This is the Tafel diagram of the PCD-MXene / WEP anti-corrosion coating prepared in Example 8 after being immersed in a 3.5wt% NaCl aqueous solution for 90 days. The results show that after 90 days of immersion, the corrosion current of the coating in Example 8 is extremely small, more than two orders of magnitude lower than that of Comparative Example 1, and the corrosion potential is higher, which indicates that the coating with the addition of PCD-MXene filler has high corrosion resistance.

[0082] The PCD-MXene / WEP anti-corrosion coating prepared in Example 8 was subjected to a scratch test and immersed in a 3.5 wt % NaCl aqueous solution for 48 h. Figure 6 Shown is the Nyquist plot of the experiment. The results show that the impedance arc radius increases slightly after the coating is immersed, which indicates that the PCD-MXene in the coating has corrosion inhibition and self-healing properties.

[0083] The above coatings were tested for coating hardness according to GB / T 6739-2022 "Determination of film hardness by pencil method for paints and varnishes", coating adhesion according to GB / T9286-2021 "Paint and varnish scratch test", coating flexibility according to GB / T 1731-2020 "Determination of flexibility of paint and putty film", and coating impact resistance according to GB / T 1732-2020 "Determination of impact resistance of paint film". The test results are shown in Table 1. It can be seen that the waterborne epoxy resin anti-corrosion coating with the addition of PCD-MXene can significantly improve the mechanical properties of the coating, which is mainly attributed to the good compatibility of PCD-MXene with WEP.

[0084] Table 1

[0085]

[0086]

[0087] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating, characterized in that: The anticorrosive coating comprises, by weight: 0.3 to 0.8 parts of PCD-MXene filler, 35 to 40 parts of waterborne epoxy resin, 45 to 55 parts of curing agent, 0.025 to 0.05 parts of body filler, and 0.02 to 0.1 parts of auxiliary agent; The preparation method of the PCD-Mxene comprises the following steps: Step 1: Add lithium fluoride to concentrated hydrochloric acid. After the reaction is complete, add Ti3AlC2 and etch the reaction while stirring. After the reaction is complete, wash with deionized water and centrifuge. Collect the precipitate, add deionized water, place in an ice water bath under nitrogen atmosphere and ultrasonicate for 1 hour, centrifuge, collect the suspension, and freeze-dry to obtain Ti3C2T x MXene powder; Step 2: Add salicylic acid and banana peel powder into deionized water, stir, and adjust the solution to neutrality with ammonia water; transfer the solution to an autoclave for hydrothermal reaction. After the reaction is completed, purify it with deionized water in a dialysis bag and freeze-dry to obtain CD powder; Step 3: Add 3-amino-1-propanol and NaOH to DMF, then add 5-chloro-1,10-phenanthroline, heat and stir until all dissolved to obtain the first solution; add CD powder to n-butanol, ultrasonicate, and add Ti3C2T x MXene powder and ascorbic acid are stirred evenly to obtain a mixed solution; the mixed solution is added to the first solution, stirred under a nitrogen atmosphere and an ice water bath, centrifuged, washed, and dried to obtain PCD-MXene powder; Step 4: Mix PCD-MXene, water-based epoxy resin, curing agent, physical filler and additives according to mass proportions to obtain PCD-MXene / WEP anti-corrosion coating.

2. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 1, characterized in that: In step 1, the mass ratio of lithium fluoride to Ti3AlC2 is (1-2): (0.5-1.5).

3. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 2, characterized in that: In step 2, the mass ratio of salicylic acid to banana peel powder is (1-3): (2-4).

4. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 3, characterized in that: The ratio of 3-amino-1-propanol to NaOH in step 3 is 1 ml: 0.75g, NaOH and 5-chloro-1,10-phenanthroline, CD, Ti3C2T x The mass ratio of MXene and ascorbic acid is 30:30:16:40:

1.

5. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 4, characterized in that: The temperature of the hydrothermal reaction in step 2 is 180-200°C.

6. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 5, characterized in that: The ultrasonic treatment time in step 3 is 5 to 10 minutes.

7. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anti-corrosion coating according to claim 6, characterized in that: The curing agent is at least one of CYDHD-220, CYDHD-520 or CYDHD-625 curing agents.

8. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anticorrosive coating according to claim 7, characterized in that: The auxiliary agent is at least one of a defoamer, a wetting agent or a dispersant.

9. The self-healing antioxidant Phen / CD-MXene / waterborne epoxy resin anticorrosive coating according to claim 8, characterized in that: The physical filler is at least one of talcum powder, mica powder or bentonite.

10. A self-healing anti-oxidation and anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating according to any one of claims 1 to 9.

Citation Information

Cited By

  • Ultrafiltration membrane for sewage treatment and preparation method thereof

    CN121401877A